Methodology Of Experimental Study Of Mastering Classical Music By Teenagers - Sobirova Oygul Alimovna (Genius Journals, 2021)
Theoretical substantiation development and experimental verification of forms and methods of using popular classics for the development of classical music by adolescents in a comprehensive school. Popular classics are a combination of the melodic basis of classical music and the most characteristic expressive means of pop music or jazz into a single whole.
Keywords: emotional drama; collective reflection; Musical storytelling; differentiation and integration of musical material